"This rally is not authorized": preventive repression and public opinion in electoral autocracies - Tertytchnaya, K (Johns Hopkins University Press, 2023)
Does preventive repression dampen or does it bolster mass support for groups that dissent despite obstruction? Although a large literature recognizes the importance of preventive repression for authoritarian stability, we know very little about its effects on public opinion. To gain traction on this question, this article draws on evidence from unusually detailed data on unauthorized and authorized protests from Russia and an original survey experiment. The author shows that when authorities engage in preventive repression, such as when they deny protest authorizations, protesters' ability to generate support is compromised. Preventive repression also conditions the effect of nonviolent demonstrator tactics on public opinion. These effects, however, are contingent on citizens' attitudes about the law and the authorities. This article's findings—which provide one of the first causal tests of the mass opinion effects of preventive repression—expand our understanding of the consequences and audiences of repression and have implications for studies of authoritarian resilience.